(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Since almost everyone has a hectic schedule due to many activities that need to be fulfilled, there is only limited time to consume, and doing laundry is often left ignored. Businesses like the selected laundry shop see an opportunity to let people (especially working ones) feel less tired and stressed doing laundry by offering laundry services such as cleaning, washing, and drying clothes. The purpose of this study is to determine the effectiveness of the marketing mix in the business performance of selected laundry shops in Bagong Silang, Caloocan City, in terms of age, gender, civil status, number of household members, socioeconomic status, place, price, product, and promotion. The results of the study reveal that the majority of the respondents are female, and ages 21 to 30 are the most active age group availing of the services in laundry shops. Most respondents are single, and in addition, most respondents are in the middle class. The assessment of the effectiveness of the marketing mix on the business performance of selected laundry shops in terms of product, price, place, and promotion is "highly effective." There is no significant relationship between the effectiveness of the marketing mix and the business performance of selected laundry shops when the profile is considered. The problems encountered by the respondents are overpricing, availability of laundry detergents, damaged or discolored clothes, and cleanliness of the clothes. Based on the results of the study, the researchers recommend enhancing the effectiveness of the marketing mix on the business performance of selected laundry shops by formulating a marketing strategy that will deal with the 4Ps (place, price, product, and promotion) as well as the problem(s) encountered by most respondents.